2017
DOI: 10.1002/rrq.204
|View full text |Cite
|
Sign up to set email alerts
|

Second‐Language Reading Difficulties Among Native Chinese‐Speaking Students Learning to Read English: The Roles of Native‐ and Second‐Language Skills

Abstract: The authors report two studies that examined how native‐ and second‐language skills were related to second‐language reading difficulties for native Chinese‐speaking fourth graders learning to read English. In study 1, 50 poor English readers with Chinese‐reading difficulties (the PB group) and 34 poor English readers without Chinese‐reading difficulties (the PE group) were compared with 53 typically developing controls on phonological awareness, rapid naming, and phonological memory. Results showed that both g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 64 publications
0
25
0
Order By: Relevance
“…Teaching materials included relevant textbooks: Letter Land ( Wendon, 2009 ; Holt, 2011 ), Root Phonics English ( Sun and Lytton, 2010 ), and Pandeng English ( Pandeng English Project Team of State Key Laboratory of Cognitive Neuroscience and Learning at Beijing Normal University, 2012 ). This training protocol has been used in previous studies ( Li et al, 2018 ; Xu et al, 2021 ). Teachers who were professionally trained in music and English language instruction at the master’s level were hired for this project.…”
Section: Methodsmentioning
confidence: 99%
“…Teaching materials included relevant textbooks: Letter Land ( Wendon, 2009 ; Holt, 2011 ), Root Phonics English ( Sun and Lytton, 2010 ), and Pandeng English ( Pandeng English Project Team of State Key Laboratory of Cognitive Neuroscience and Learning at Beijing Normal University, 2012 ). This training protocol has been used in previous studies ( Li et al, 2018 ; Xu et al, 2021 ). Teachers who were professionally trained in music and English language instruction at the master’s level were hired for this project.…”
Section: Methodsmentioning
confidence: 99%
“…Past research involving L2 students have suggested positive effects of phonics instruction on reading and spelling in L2 (Li et al, 2018;Vadasy & Sanders, 2012).…”
Section: The Present Studymentioning
confidence: 98%
“…Past research involving L2 students have suggested positive effects of phonics instruction on reading and spelling in L2 (Li et al, 2018; Vadasy & Sanders, 2012). However, no study has examined the effects of shared book reading integrated with GPC instruction on L2 literacy skills among ESL students.…”
Section: The Present Studymentioning
confidence: 99%
See 2 more Smart Citations